CASSAVA PEEL BIOSORBENT (Manihot utilissima) FOR REMOVAL CHROMIUM (VI) WITH MICROBIAL FUEL CELL SYSTEM OF COMBINATION TECHNIQUES BIOADSORPTION AND BIOELECTROCHEMISTRY - Rachman, Rahadian Abdul; Karima, Ulva Tri Ita Martia; Pambudi, Agung Bagus; Jovita, Stella; Kurniawan, Fredy (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.588, 2017)
Cassava peel biosorbent as heavy metal adsorbent of chromium (VI) has active organic compound. The active cellulose compound for adsorption of chromium metal is evidenced by FTIR activated carbon having an absorbent band at 3412 cm -1 wave number which is an OH functional group reinforced by absorbing band at 1323 cm -1 which is OH (bending) and 1109 cm -1 Which indicates the presence of CO vibration from secondary OH, and the absorption band at 3000-2750 cm -1 which is CH sp 3 . The effect of combination technique on the best microbial fuel cell system is bioelectrochemical-biosorption method. The result of the reduction of Cr (VI) content by the bioelectrochemical-biosorption method on the best pH (1,4,7,10 and 13) variations was at pH 1 with a 10 min contact time of 0.285 mg / L, 15 minutes at 0.253 mg / L, and 20 minutes of 0.177 mg / L in accordance with Standard of Industrial Waste Water Quality Standard of KEMEN LH RI. 5 year 2014 is the maximum limit of chromium levels is 0.5 mg / L.